Mobile Operator Advertising: Critical Discourse Analysis - Kharis Marpurdianto (Linguistic, English Education and Art (LEEA) Journal, 2020)
This research examines contextual meaning contained in the mobile operator’s advertisement in Indonesia. It focuses on how the form of cohesion and coherence, the form of word choice, and the grammatical element found in mobile operator’s advertising discourse in Indonesia. A descriptive qualitative method with the content analysis technique is used as the methodology in this study. Using these methods, the researcher can give a wider understanding of the linguistic lessons through the theory of critical discourse analysis. The data is taken from mobile operator’s advertisement and some books and journals. As a result of this study, the researcher found a form of word choice, cohesion and coherence as well as grammatical elements that emerged in mobile operator’s advertisement discourse including non-standard variety. The advertisement language replicates from competitors that feature cheap phone rates. Moreover, there is a contextual meaning in word choice of Indonesian discourse in mobile carrier advertisement. Keywords: Advertisement, Mobile Operator, Critical Discourse Review.